Adaptable interaction between aquaporin‐1 and band 3 reveals a potential role of water channel in blood CO2 transport. Issue 10 (19th September 2017) - Hsu, Kate; Lee, Ting‐Ying; Periasamy, Ammasi; Kao, Fu‐Jen; Li, Li‐Tzu; Lin, Chuang‐Yu; Lin, Hui‐Ju; Lin, Marie
ABSTRACT: Human CO2 respiration requires rapid conversion between CO2 and HCO3 − . Carbonic anhydrase II facilitates this reversible reaction inside red blood cells, and band 3 [anion exchanger 1 (AE1)] provides a passage for HCO3 − flux across the cell membrane. These 2 proteins are core components of the CO2 transport metabolon. Intracellular H2 O is necessary for CO2 /HCO3 − conversion. However, abundantly expressed aquaporin 1 (AQP1) in erythrocytes is thought not to be part of band 3 complexes or the CO2 transport metabolon. To solve this conundrum, we used Förster resonance energy transfer (FRET) measured by fluorescence lifetime imaging (FLIM‐FRET) and identified interaction between aquaporin‐1 and band 3 at a distance of 8 nm, within the range of dipole‐dipole interaction. Notably, their interaction was adaptable to membrane tonicity changes. This suggests that the function of AQP1 in tonicity response could be coupled or correlated to its function in band 3‐mediated CO2 /HCO3 − exchange. By demonstrating AQP1 as a mobile component of the CO2 transport metabolon, our results uncover a potential role of water channel in blood CO2 transport and respiration.—Hsu, K., Lee, T.‐Y., Periasamy, A., Kao, F.‐J., Li, L.‐T., Lin, C.‐Y., Lin, H.‐J., Lin, M. Adaptable interaction between aquaporin‐1 and band 3 reveals a potential role of water channel in blood CO2 transport. FASEB J. 31, 4256–4264 (2017). www.fasebj.org